Socioeconomic determinants of older rural women involved in CSO of Malaysian fisheries society - Zainalaludin, Zumilah; Saidi, Norehan (Human Resource Management Academic Research Society, 2024)
This study mainly aims to calculate the socioeconomic determinants that predict older respondents. A total of n=310 respondent reported, and three Hos tested through Binary Logistic Regression Model 1-3, respectively. All Hos were rejected because all models fit and significant (p<0.05). This study assumes that older respondents are active as they age. Hence, it is important to identify the socioeconomic backgrounds of active older women living in rural areas to develop effective programs and policies on active ageing